Secretogranin II impairs tumor growth and angiogenesis by promoting degradation of hypoxia‐inducible factor‐1α in colorectal cancer. Issue 12 (26th July 2021) - Fang, Chao; Dai, Lei; Wang, Cun; Fan, Chuanwen; Yu, Yongyang; Yang, Lie; Deng, Hongxin; Zhou, Zongguang
Abstract : Distant metastasis is a major cause of death in patients with colorectal cancer (CRC) but the management of advanced and metastatic CRC still remains problematic due to the distinct molecular alterations during tumor progression. Tumor angiogenesis is a key step in tumor growth, invasion and metastasis. However, the signaling pathways involved in angiogenesis are poorly understood. The results of the present study showed that secretogranin II (SCG2) was significantly downregulated in malignant CRC tissues, and higher expression of SCG2 was correlated with longer disease‐free survival and overall survival of CRC patients. The results of an animal study showed that ectopic expression of SCG2 significantly inhibited CRC tumor growth by disrupting angiogenesis. Furthermore, the inhibition of expression of vascular endothelial growth factor (VEGF) by SCG2 and rescue of VEGF effectively blocked SCG2‐induced inhibition of angiogenesis. Investigations into the underlying mechanism suggested that SCG2 promoted degradation of hypoxia‐inducible factor (HIF)‐1α by interacting with the von Hippel–Lindau tumor suppressor in CRC cells. Blocking of degradation of HIF‐1α effectively attenuated the SCG2‐mediated decrease in expression of VEGF in CRC cells. Collectively, these results demonstrated that treatment with SCG2 effectively inhibited CRC tumor growth by disrupting the activities of HIF‐1α/VEGF, thereby clarifying the anti‐tumor and anti‐angiogenesis roles of SCG2 in CRC, while providing a novel therapeutic target and a potential prognostic marker of disease progression. Abstract : Tumor angiogenesis is a key step in tumor growth, invasion and metastasis. However, the signaling pathways involved in colorectal cancer (CRC) angiogenesis are poorly understood. Here we show that secretogranin II (SCG2) was significantly downregulated in malignant CRC tissues and higher expression of SCG2 correlated with longer disease‐free survival and overall survival of patients with CRC. SCG2 impaired tumor growth and angiogenesis by inhibiting vascular endothelial growth factor expression and promoting hypoxia‐inducible factor‐1α degradation. Therefore, SCG2 may serve as a novel therapeutic target and a potential prognostic marker of disease progression in patients with CRC.